The Influence of Economic Literacy and Digital Literacy on Consumptive Behaviour of Students - Bayu Surindra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the influence of economic literacy and digital literacy on the consumptive behavior of Nusantara PGRI University of Kediri students during the COVID-19 pandemic. While the problems contained in this research are how well the level of student understanding related to economic literacy and digital literacy that has been obtained so far in lectures. The method used in this research was quantitative research methods. The sample used in this study was students of the Economic Education Study Program, Nusantara PGRI University of Kediri, totaling 36 students, and used purposive random sampling. Collecting data by distributing questionnaires via Google form to the respondents. The data analysis technique was multiple regression analysis using SPSS version 23 software. From the results of the multiple linear regression test, it is known that partially the economic literacy variable is 0.028 <0.05, showing a significant influence between economic literacy and student consumptive behavior. Furthermore, the digital literacy variable is 0.599 > 0.05, indicating that there is no significant effect between digital literacy and student consumptive behavior. And from the results of the multiple linear regression test simultaneously of 0.034 <0.05, indicating a significant influence between the variables of economic literacy and digital literacy on the consumptive behavior of students